Simulation and Design of an Intelligent Mobile Robot for Fire Fighting - Chor, Keong Seng (2003)
The application of traditional frangible glass panel and automatic system such as smoke detector or heat detector requires a human response to realise the existence of fire and to perceive and determine its severity. However, fire-fighting system such as sprinkler causes the damage of the property and also injury and panic due to the water sprayed out when the system trigged. Thus to avoid such incident, a mobile robot with fire detection capability and fire fighting system to perform fire-fighting purpose is a new technology to reduce subsequent damage and secure life before the fire engine to attend. A navigation system base on fuzzy logic controller (FLC) is developed for the mobile robot in an ambiguous situation for fire fighting purpose. A method of Path Recognition Algorithms (PRA) providing robots the autonomous ability to judge purpose of action likes human base on the input sensors from the environment. Multiple fuzzy behaviours by fuzzy logic method have been developed to allow the robot over come some of the possible obstacles and resistances for the robot to navigate in unknown environment. Behaviours have been integrated with arbitration strategy to determine the appropriate behaviours by priority method with preset data. An ultrasonic sensor and an infrared thermal sensor were mounted on a 360 degree rotated stepper motor to scan distance between the robot and its immediate obstacles and fire source around its environment. A fuzzy base computer animation in virtual reality is developed to simulate a simple in-door environment for fire fighting purpose and a systematic implementation of real-time simulation of the mobile robot is presented. However traveling in such region to the target location, there exist some unknown obstacles for the mobile robot especially in real-world environment with unknown map and unpredictable obstacle location, thus the control algorithms must be able to promptly react upon the unpredictable. The simulation result of this study indicated that application of FLC in mobile robot could be a suitable system for fire detection and fire fighting task in an unknown environment. More comprehensive study in behaviour coordination will be the major focus to ensure smoother robot navigation and more effective fire detection capability. Keywords: (Fuzzy logic control, mobile robot, part recognition algorithms)